ChemInform Abstract: Ternary Bismuthides Li3REBi2 (RE: Ce, Pr, Sm, Gd) with Li3LaSb2‐Type Structure. Issue 3 (January 2015) - Winter, Florian; Poettgen, Rainer
Abstract The title compounds are prepared from the elements (Nb tubes, 1273 K for 6 h and 923 K for 72 h) and characterized by powder XRD.